Focus on Italian Verbal Morphology in Multilingual Classes. Issue 1 (18th August 2015) - Whittle, Anna; Lyster, Roy
Abstract: This quasi‐experimental study investigated the effects of form‐focused instruction on Italian verbal morphology (first‐ and second‐person singular forms and third‐person plural forms of the present indicative) in a multilingual primary school in Italy. The 10‐hour instructional treatment was distributed over fifteen 40‐minute biweekly lessons in three intact Grade 2 classes comprising native and nonnative speakers of Italian. The instruction was designed to increase the saliency and frequency of the target forms while providing opportunities for oral production practice and corrective feedback. To measure the effects of instruction, 14 Chinese L1 students from the three classes comprised the experimental group, while a similar group of nine Chinese L1 students attending Grade 2 classes at the same school during the following year served as the comparison group. Both groups participated in oral elicitation tasks that served as pre‐ and posttests. A one‐way analysis of variance showed a strong treatment effect for the form‐focused instruction and qualitative analysis of the production data revealed developmental strategies specific to the experimental group. Open Practices: This article has been awarded an Open Materials badge. All materials are publicly accessible in the IRIS digital repository athttp://www.iris-database.org . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki